2006
DOI: 10.1007/s10546-006-9133-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial representativeness of single tower measurements and the imbalance problem with eddy-covariance fluxes: results of a large-eddy simulation study

Abstract: A large-eddy simulation (LES) study is presented that investigates the spatial variability of temporal eddy covariance fluxes and the systematic underestimation of representative fluxes linked to them. It extends a prior numerical study by performing high resolution simulations that allow for virtual measurements down to 20 m in a convective boundary layer, so that conditions for small tower measurement sites can be analysed. It accounts for different convective regimes as the wind speed and the near-surface h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
95
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 34 publications
(56 reference statements)
10
95
1
1
Order By: Relevance
“…However, net radiation measurements are insensitive to such outer-layer modulations. Whether this mechanism alone may explain the lack of surface energy balance closure is subject to some debate (Steinfeld et al 2007). For example, the performed analysis showed that during a 6-min sweeping event of dry and cold air from the outer layer, the local latent heat flux actually increased (not decreased).…”
Section: Discussionmentioning
confidence: 99%
“…However, net radiation measurements are insensitive to such outer-layer modulations. Whether this mechanism alone may explain the lack of surface energy balance closure is subject to some debate (Steinfeld et al 2007). For example, the performed analysis showed that during a 6-min sweeping event of dry and cold air from the outer layer, the local latent heat flux actually increased (not decreased).…”
Section: Discussionmentioning
confidence: 99%
“…This is because turbulent transport is not well resolved by the numerical grid in this region due to the limited eddy size. Data analysis has shown that the subgrid-scale flux contribution is below 5 % of the total flux above the third vertical grid layer (see also Steinfeld et al 2007). Therefore, the subgrid-scale flux contribution is not considered further in calculations of the turbulent flux.…”
Section: Methodsmentioning
confidence: 97%
“…Detailed descriptions of PALM have been provided by Raasch and Etling (1998) and Raasch and Schröter (2001). PALM has been successfully applied for investigations of the neutrally (Letzel et al 2008) and weakly stably stratified boundary layer (Beare et al 2007;Steinfeld et al 2007) as well as the homogeneously heated (Schröter et al 2000;Raasch and Franke 2011) and heterogeneously heated CBL (Raasch and Harbusch 2001;Letzel and Raasch 2003;Inagaki et al 2006;Steinfeld et al 2008;Maronga and Raasch 2013) and is therefore well suited for this study.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Also in recent studies, it was found that fluxes averaged over long time periods (Finnigan et al 2003;Mauder and Foken 2006;Sakai et al 2001) or spatially averaged fluxes (Inagaki et al 2006;Kanda et al 2004;Steinfeld et al 2007) could close the energy balance. These hypotheses were not investigated during EBEX-2000.…”
mentioning
confidence: 90%